A Neutral White Locus. Issue 1 (2nd January 2019) - Luo, Ming Ronnier; Ma, Shining
ABSTRACT: It was reported recently that chromaticities of neutrality across different correlated color temperatures were not located on the Planckian locus. This study is intended to establish a neutrality locus by comparing lightings presented in two adjacent viewing cabinets. For 61 light stimuli at 167 cd/m 2 along seven iso-color temperature lines, each including seven to nine levels of deviation from the Planckian locus, Duv was investigated. Seventeen observers used the method of limits to determine the neutral white locus and the most neutral white. The results showed that the neutral whites were located between −0.010 and −0.015 units below the Planckian locus. It was also found that a chromaticity close to 5900 K appeared to be the unique white on the newly established neutral white locus.